ETIKA ISLAM DALAM RUANG DIGITAL (TANTANGAN DAN PELUANG TRANSFORMASI PENDIDIKAN ISLAM) - Nur Amalina Abdul Rahman; St Nurhayati; Nurul Ilmi Adyana; Jeny Rheka (STKIP Pesisir Selatan, 2026)
This study aims to analyze Islamic ethics within the digital space and examine its implications for the transformation of Islamic education. The rapid expansion of digital technology has reshaped educational interactions, learning cultures, and value transmission, posing both ethical challenges and strategic opportunities for Islamic educational institutions. This article seeks to position Islamic ethical values as a normative and pedagogical foundation in responding to digital disruption. This research employs a qualitative approach through library research. Data were collected from recent scholarly journals, authoritative books, and relevant academic documents published within the last five years. The analysis was conducted using a conceptual and thematic approach, focusing on Islamic ethical principles and their relevance to contemporary digital educational practices. The findings indicate that the digital space presents significant ethical challenges for Islamic education, including moral degradation, information disinformation, weakening of educational authority, and shifts in learners’ value orientations. However, digital transformation also offers opportunities to reconstruct Islamic education through ethical digital literacy, value-based pedagogical innovation, and strengthening the role of educators as moral guides in virtual learning environments.